Electrical conductivity and single oscillator model properties of amorphous CuSe semiconductor thin film - Yakuphanoğlu, Fahrettin; Viswanathan, C. (Elsevier Science Bv, 2007)
The structural, optical dispersion and electrical conductivity properties of the CuSe thin film have been investigated using X-ray diffraction, electrical and optical characterization methods. X-ray diffraction results indicate that CuSe thin film has an amorphous structure. The electrical conductivity of the CuSe film increases with increasing temperature. The activation energy and room temperature conductivity values of the film were found to be 1.32 meV and 3.89 x 10(-3) S/cm, respectively. The refractive index dispersion of the thin film obeys the single oscillator model and single oscillator parameters were determined. The E-o, n(infinity), and S-o values of the CuSe thin film were found to be 5.08 eV, 3.55 and 1.92 x 10(14) m(-2), respectively. The obtained results suggest that CuSe film is an amorphous semiconductor. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: amorphous semiconductor; conductivity; absorption; X-ray diffraction